"It Can’t Just be One": Canadian Black Youth Perspectives on Representation and Belonging in Public Libraries - Matthews, Amber; Thomas, Sandie (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2026)
This study employed narrative inquiry and critical race approaches to explore Black youth's perceptions and experiences of Canadian public library programs and materials. In response to calls in Canada's Anti-Racism Strategy (2024) and Ontario's Anti-Black Racism Strategy (2025) for social service institutions to address anti-Black racism, the research examined Black youth experiences in public libraries and how these experiences relate to anti-Black racism in education and social service settings. The study was conducted in London, Ontario, with Black youth aged 13 to 24 and parents of youth using a community-based participatory research approach in partnership with the Where We Are Now (WEAN) Black Community Centre & London Black Community Public Library. Data were collected through semi-structured interviews and an arts-based qualitative tool (personal meaning mapping) with 21 participants: 14 youth and seven parents. Findings reveal that, while many youth reported positive early memories of public libraries often associated with family members, they also identified significant challenges in belonging and feeling welcome. These challenges stem from underrepresentation in library materials and staff, from institutional approaches to inclusion that participants experienced as performative rather than transformative, and from experiences of microaggressions and bias. The study proposes a collaborative, community-based research framework applicable across library and information science contexts to examine broader challenges related to representation, belonging, and performative inclusion.